Analyzing trip cost with no late arrival under car-following model. (March 2015) - Tang, Tie-Qiao; Huang, Hai-Jun; Wu, Wen-Xiang; Wu, Yong-Hong
Abstract: In this paper, we use a car-following model to explore each individual commuter's trip cost without late arrival from the analytical and numerical perspectives. Our results show that each individual commuter's trip cost and the total cost are related to each commuter's time headway at the origin when the road is long enough and the number of commuters is large enough.